Career Lesbians: Getting Hired for Not Having Kids? - Stijn Baert (Institute for the Study of Labor (IZA), 2013)
Using a field experiment, we investigate whether discrimination based on women's sexual orientation differs by age and family constraints. We find weakly significant evidence of discrimination against young heterosexual women. This effect is driven by age (and fertility) rather than by motherhood. We do not find any unequal treatment at older ages. This age effect is consistent with our theoretical expectation that, relative to lesbian women, young heterosexual women are penalised for getting children more frequently and taking on, on average, more at-home-caring tasks.
Keywords: C93; J13; J16; J71; 330; labour market discrimination; sexual orientation; motherhood